(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article examines the increase in capital of commercial banks and the factors influencing it on the basis of theoretical and practical data. Also, based on the study of foreign experience, it is argued that the increase in asset quality in banks will directly improve the quality of credit services provided by banks, reduce problem loans and the use of credit scoring system. A number of specific aspects of the use of credit scoring system in improving the quality of assets of commercial banks have been studied in detail on the basis of theoretical and practical data, scientific proposals and practical recommendations have been developed on the basis of author’s approaches